Assessment of Condition of Prescription of Panoramic Radiography According to the FDA Guidelines by General Dentists in Yazd in 2019 - Masoud Esmaeili; Moein Soltanzade; Motahareh Kaboodsaz Yazdi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2020)
Introduction: Panoramic radiography is a valuable tool in the diagnosis of maxillofacial lesions, due to the visibility of all the teeth, alveolar bone and TMJ. This study was performed to evaluate the status of panoramic radiography in accordance with FDA rules in general dentists in Yazd in 2019. Methods: In this descriptive cross-sectional study, 170 general dentists (86 women and 84 men) working in Yazd in 2019 were completed questionnaires, including two parts: the first part consisted of demographic information( age, gender, number of years of graduation, university of Education), and the second part was specific questions in three areas: survey (28 questions), case introduction (6 cases) and diagnostic value (6 questions) about panoramic radiography. The collecting data were entered into SPSS software version 18 and analyzed using t-test and linear regression. Results: The mean score of the survey questions was 103/05±12/86, the mean score of case questions was 5/76±2/22 and the mean score of diagnostic value questions was 8/12±2/56, respectively. There was a significant difference between the mean score of diagnostic value questions in terms of participation in radiology retraining courses (p=0.016). There was a statistically significant relationship between the mean score of diagnostic value questions with the age of dentists (p=0.015) and the mean score of survey questions (p=0.029) and mean score of case questions (p=0.039) with the university of study. Conclusion Panoramic radiography prescriptions in general dentists working in Yazd, in some cases, do not comply with the FDA guidelines for prescribing panoramic radiography, and further training in this field seems necessary.